ANALISIS KONSEP OTONOMI DAERAH BERDASARKAN PERKEMBANGAN KONSTITUSI DI INDONESIA - Syahrul Ibad (HUKMY : Jurnal Hukum, 2025)
This study discusses regional autonomy in Indonesia, which is related to the concept and theory of local government and how it is applied in the implementation of regional government in Indonesia. Because local government is part of the state, the concept of local government cannot be separated from the concepts of state sovereignty in unitary and federal systems, as well as centralization, decentralization, deconcentration, and assistance tasks. This research was conducted through library research. This research is normative or doctrinal in nature, where data will be obtained from reading or analyzing written materials. Thus, it produces: First, regional autonomy is a manifestation of the creation of democracy in Indonesia. Second, the power of the central government is so absolute and centralistic. Third, regional autonomy as a manifestation of local government, where regional autonomy is related to autonomous regional government (Self-Local Government). Fourth, some concepts of government exist in the Federal State and the division of power where theoretically in a unitary state like Indonesia, both original and residual powers should be at the center. Therefore, it can be said that the government in Indonesia operates while still accommodating two, namely centralization and decentralization.